BUSINESS RISKS LEVEL OF CONSEQUENCES IDENTIFICATION: CASE OF WOMEN FORMAL FASHION SMEs - Elsa Putri, Ghaissani
The fashion industry is one of the creative industry sectors in Indonesia that contributes high to the gross domestic product (GDP). To be more specific, most of the fashion industry companies are dominated by SMEs (Small and Medium Enterprises). The growth of micro, small and medium businesses from the fashion industry in Indonesia is very fast and therefore this industry must face the challenges of increasing competitiveness. The development of the fashion creative industry in Indonesia is still running independently and has not made a priority scale of the aspects to be developed, so that it seems sporadic and not systematic. Based on a study, inexperienced people (in this case, fashion SMEs) usually do not see the risks that might occur, or if they do, they underestimate the possibility that they will be affected by them. The main risk for any organization is business risk. This study aims to identify business risks and their level of consequences in women's formal fashion SMEs. This research will use a qualitative approach with in-depth interview methods. To achieve this goal, researchers interviewed 10 companies. Based on the results of interviews, most respondents have not systematically identified risks, but there are some who have done simple identification of risks early. Known from the five risk categories according to the reference literature, each has a different level of impact. Strategic risk has a medium impact, while operational, reputation and financial risks have a tiered impact depending on the type of risk. Whereas socio-political risk has the least impact. This level of consequence is strongly influenced by the condition of the business scale, business models, vision and mission. Based on research, there are a number of recommendations suggested by researchers, even though by considering the scale of SME businesses that are considered not to require specific and structured risk identification, SMEs still need to identify risks through recording the pattern of risks that have occurred in the company. Thus, it is expected that in the future the company can know the potential risks that may occur so as far as possible to minimize the impact caused